The Role of -Ing in Contemporary Slavic Languages - Marta Lackova (Communications - Scientific letters of the University of Zilina, 2012)
The article deals with words of English origin (with the terminal suffix -ing) which have penetrated into contemporary Slavic languages. The general introduction into the characteristics of -ing lexemes in the English language as well as principles of lexical unit adaptation are provided. The main emphasis is put on orthographic, morphological, word-formation and semantic adaptation of the lexical units in the Slovak, Russian and Czech languages.